Safeguarding Beneficial Insects: Strategies and Innovations for Conservation Amidst Growing Threats - Reddy, K. S. Nikhil; Nagarjuna, T. N.; Tippimath, Sadashiva; Shwetha, G. S.; Sugeetha, G.; Nagaraju, M. C. (International Journal of Bio-resource and Stress Management, 2025)
Beneficial insects, including pollinators, pest predators and decomposers, are vital for ecosystem health and agricultural productivity. This review examines the decline of key species such as honeybees, monarch butterflies, ladybugs, and rusty patched bumblebees. Their populations are threatened by habitat loss, pesticide use, climate change, and invasive species. Honeybees are suffering from diseases and pesticide exposure, while monarch butterflies face challenges from habitat destruction and shifting climates. Ladybugs and lacewings are in decline due to similar pressures, and rusty patched bumblebees are nearing extinction. Addressing these declines is crucial for maintaining biodiversity, crop yields, and ecological balance. The current conservation strategies, including habitat preservation through protected areas, habitat management and restoration and improved pesticide management are reviewed. It emphasizes the need to integrate climate change mitigation, public awareness, and education into conservation efforts. Emerging technologies such as Geographic Information Systems (GIS) offer new opportunities for habitat modelling and pest management, while strengthening policies can better address environmental stressors. Effective conservation requires a comprehensive approach that combines scientific advances with robust policies and community engagement. Immediate and coordinated action is essential to address these challenges and ensure the resilience and continued contribution of beneficial insects. By implementing transformative policies and fostering public involvement, we can support the long–term sustainability of these vital species amidst a rapidly changing world.